2021
DOI: 10.1016/j.cub.2021.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Spinal sensory neurons project onto the hindbrain to stabilize posture and enhance locomotor speed

Abstract: Highlights d Rostralmost CSF-cNs form inhibitory synapses onto occipital motor neurons d Ventral CSF-cNs inhibit reticulospinal neurons driving fast and powerful locomotion d Dorsal CSF-cNs inhibit reticulospinal neurons eliciting slow and refined locomotion d Rostral CSF-cN inhibitory sensory feedback enhances speed, power, and posture

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 114 publications
(167 reference statements)
1
16
2
6
Order By: Relevance
“…To test whether these inputs were monosynaptic in nature, we selected one square in the 4 3 4 grid and illuminated it with a 20-Hz train of five 20-ms pulses. 35 pMNs received reliable V1 input during this high-frequency stimulation at segments 0 and 1, but not segment 5 (Figure S4A). For all cells (5/5), IPSCs were evoked at a consistent latency with low jitter (Figure S4B).…”
Section: V1 Neurons Inhibit Motor Neurons Locallymentioning
confidence: 98%
See 1 more Smart Citation
“…To test whether these inputs were monosynaptic in nature, we selected one square in the 4 3 4 grid and illuminated it with a 20-Hz train of five 20-ms pulses. 35 pMNs received reliable V1 input during this high-frequency stimulation at segments 0 and 1, but not segment 5 (Figure S4A). For all cells (5/5), IPSCs were evoked at a consistent latency with low jitter (Figure S4B).…”
Section: V1 Neurons Inhibit Motor Neurons Locallymentioning
confidence: 98%
“…Recent studies have pointed to an important role of CSF-cNs, another inhibitory, ipsilateral, and ascending spinal population (CSF-cNs), in regulating power of locomotion in response to spinal curvature. 9,35,62,63 In the future, it will be extremely relevant to study how these ascending sensory pathways are integrated for effective motor control.…”
Section: V1 Affects Sensory Neurons Broadlymentioning
confidence: 99%
“…In zebrafish larvae, CSF-cNs send an ipsilateral ascending axon from two to six segments that synapse onto premotor interneurons involved in slow locomotion, onto primary motor neurons that innervate the entire ventral musculature, and interneurons involved in sensory-motor gating ( Figure 2C ). Moreover, the rostral most CSF-cNs contact large reticulospinal neurons of the hindbrain, that in turn send descending motor commands to the spinal cord ( Figure 2C ) ( Wu et al, 2021 ), suggesting that the contractile activity of these structures promotes proper axial morphogenesis ( Zhang et al, 2018 ). Additionally, adult pkd2l1 zebrafish mutant develop a moderate spine curvature but did not resemble the motile cilia mutant phenotype.…”
Section: Emerging Roles Of Genetic Factors Related To Scoliosis Devel...mentioning
confidence: 99%
“…In addition, light stimulation of cerebrospinal fluid–contacting neurons (CSF-cNs) in zebrafish showed that GABAergic sensory neurons in the spinal cord provide strong inhibitory feedback to the escape circuit during active movement to maintain balance (Hubbard et al, 2016 ). A recent analysis that used functional anatomy and optogenetics-assisted mapping showed that CSF-cNs can generate synapses on the axons of reticulospinal neurons including Mauthner cells and V2a neurons, and relay their information to the higher-level centers of the hindbrain to stabilize posture and increase movement speed (Wu et al, 2021 ).…”
Section: Optogenetics Neuromodulationmentioning
confidence: 99%